2015
DOI: 10.1039/c5ra20060a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and sulfur codoped graphene quantum dots as a new fluorescent probe for Au3+ ions in aqueous media

Abstract: The N and S codoped GQDs can be used as a promising label free fluorescent probe for the sensitive and selective detection of Au3+ in aqueous media, which provides a new application of the functionalized GQDs to the detection of metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 48 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…The top-down methods are based on breaking large carbon structures, such as graphene, graphene oxide, or fullerenes, into nanoparticles using physical or chemical means, for instance, acid oxidation, electrochemical, and hydrothermal . In the bottom-up routes, GQDs are formed from organic precursors with good controllability, in which nitrogen doping is one of the most common strategies to improve GQD optical properties …”
Section: Introductionmentioning
confidence: 99%
“…The top-down methods are based on breaking large carbon structures, such as graphene, graphene oxide, or fullerenes, into nanoparticles using physical or chemical means, for instance, acid oxidation, electrochemical, and hydrothermal . In the bottom-up routes, GQDs are formed from organic precursors with good controllability, in which nitrogen doping is one of the most common strategies to improve GQD optical properties …”
Section: Introductionmentioning
confidence: 99%
“…Au 3+ ions, a notable heavy metal, have received great attention in chemistry and biology during recent decades and have been widely used in gold plating, 1 environmental studies, 2 anticancer agents, 3 nanomaterials, efficient catalysts, biological sensors, and drug/gene delivery systems based on their unique chemical properties and high biocompatibility. 47 In addition, these ions have also been developed for application in the jewelry industry.…”
Section: Introductionmentioning
confidence: 99%
“…Au 3+ ions, a notable heavy metal, have received great attention in chemistry and biology during recent decades and have been widely used in gold plating, environmental studies, anticancer agents, nanomaterials, efficient catalysts, biological sensors, and drug/gene delivery systems based on their unique chemical properties and high biocompatibility. In addition, these ions have also been developed for application in the jewelry industry . Studies have shown that Au 3+ ions can be used to prepare reduced graphene oxide/Au nanoparticles (NPs), drugs, and catalysts to detect dopamine, ascorbic acid, and uric acid; to treat tuberculosis and rheumatoid arthritis; and to activate carbon–carbon triple bonds. Although Au 3+ ions have versatile roles in materials science and biological systems, studies have demonstrated that Au 3+ ion-based drugs exhibit potential toxicity at certain concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…The statistic result from TEM image indicated that the particle sizes were 2–7 nm, as shown in the inset of Figure 1 a. From the HRTEM image in Figure 1 b, clear lattice fringes demonstrate the well-crystalline structure, and the autocorrelated HRTEM lattice image shows a 0.227-nm lattice fringe assigned to the (1120) lattice fringes of graphene [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%